Transforming the law : - Susskind, Richard (Oxford university press, 2000)
This is the latest book from law and technology guru Richard Susskind, author of the best-selling The Future of Law. It brings together in one volume eleven significant essays on the application of IT to legal practice and the administration of justice, including Susskind's very latest thinking on key topics like knowledge management and the impact of electronic commerce.